Differences in Ferritin Levels and Menstrual Disorders between Vegetarian and Non-Vegetarian Women in Denpasar - Fatinah Shahab (Miracle Journal Get Press, 2025)
Iron deficiency is a significant nutritional challenge for women of reproductive age, especially those who follow a vegetarian diet. Ferritin, as a key indicator of iron reserves, plays an important role in diagnosing latent iron deficiency, which can negatively affect reproductive health, including causing menstrual disorders. This study compares ferritin levels and the incidence of menstrual disorders between 50 vegetarian and 50 non-vegetarian women aged 18–45 years in Denpasar City. Ferritin levels were measured using the ELISA method, while data on menstrual disorders were collected through the Menstrual Symptom Questionnaire (MSQ). The data were analyzed using independent t-tests, chi-square tests, and multivariate logistic regression (α=0.05). The study found that the average ferritin level in vegetarian women (21.4 µg/L) was significantly lower than in non-vegetarian women (36.9 µg/L; p<0.001), and the prevalence of menstrual disorders such as dysmenorrhea and irregular cycles was higher among vegetarians. Logistic regression analysis confirmed that a vegetarian diet (odds ratio [OR]=2.98; p=0.014) and ferritin levels below 30 µg/L (OR=3.62; p=0.007) were significant predictors of menstrual disorders. Thus, a vegetarian diet and low ferritin levels are identified as key risk factors for menstrual disorders in women of reproductive age. These findings underscore the importance of monitoring ferritin status and applying appropriate nutritional strategies for vegetarian women to help support optimal reproductive health.